Monoclonal antibody manufacturing in transgenic plants - myths and realities - Hood, E.E.; Woodard, S.L.; Horn, M.E.
The number and types of antibodies expressed in plants has increased steadily since the first reports of this accomplishment in the 1980s, illustrating the versatility of plants as a production system for antibodies. Many recent reviews have detailed the antibody forms that have been derived from plant expression systems. This contribution focuses on the remaining challenges to develop plant-derived therapeutic antibodies into products, and some of the progress that is being made in addressing these challenges. Plants are proving to be a versatile system for the production of antibodies, but some challenges remain
Keywords: MAB; TRANSGENIC PLANTS; MOLECULAR FARMING; GLYCOSYLATION; CONTAINMENT; MANUFACTURING CAPACITY; AVIDIN